Timely MMR Vaccination in Infancy: Influence of Attitudes and Medical Advice on the Willingness to Vaccinate - Schönberger, K.; Ludwig, M.-S.; Wildner, M.; Kalies, H. (Klinische Pädiatrie, 2012)
In light of the failure to eliminate measles by 2010, the closure of any gaps in immunisation coverage is of paramount importance to interrupt transmission and to protect vulnerable individuals. Not only vaccination-critical attitudes of parents but furthermore the medical advice by physician in charge influence the vaccine uptake. 3 groups of factors which potentially influence parental decisions on child vaccination were analysed by univariable and multivariable logistic regression for the timely uptake of the first and the second dose of measles vaccination: parents’ attitudes towards immunization, the influence of medical and laypersons and the influence of the advice of a medical doctor. A total of 3 041 children were eligible for the analysis. 53.0% of these received the first and 42.9% the second MMR dose in time. If parents considered that vaccinations are important and protective as well as the consulted physician advices towards vaccinations, children had significantly higher chances of a timely vaccination. Whereas, if parents were afraid of vaccinations or get advised by an alternative practitioner, the children had lower chances of being vaccinated in time. If medical providers help parents to reduce uncertainties about vaccination the chance for children to be vaccinated in time increased. It appeared that there still are unmet information needs after the medical consultation. By and large the medical advice plays an important role for vaccination uptake and its timing. In order to raise the vaccination rates further target-population specific approaches are needed
Keywords: timely measles vaccination; medical advice; parental attitudes; children